Hubungan Durasi Bermain Game Online Dengan Tingkat Nyeri Punggung Bawah Pada Komunitas E-Sport - Reasius Bobby Hudson Rewasan; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro3; Ahmad Abdullah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Low back pain (LBP) is one of the musculoskeletal disorders caused by poor body activities.This study aims to analyze the relationship between the duration of playing online games with the level of LBP. Methods: The independent variable in this study is the duration of playing the game, and the dependent variable is the level of low back pain There were 15 respondents in this study using purposive sampling technique. The design of this study used a one group test at the same time. Results: The results of this study are p-value = 0.015 (p <0.05) meaning that there is correlations between the duration of playing online games with level of lower back pain in the barokah e-sport game community, mojoroto kediri district. Conclusion: 1. The average playing game time, for each player is 120 hours/month, and be categorized as heavy user.2. The average pain scale of lower back pain for each players is 3,73 or mild pain.